Synthesis of Enantiopure tert-Butanesulfinamide from tert-Butanesulfinyloxazolidinone - Qin, Yong; Wang, Canhui; Huang, Zhiyan; Xiao, Xue; Jiang, Yaozhong (Journal of organic chemistry, 2004)
A three-step procedure for the preparation of enantiopure tert-butanesulfinamide 6 in 51% overall yield is described starting from (1R,2S)-N-Cbz-1,2-diphenylaminoethanol. The key step is the reaction of tert-butylmagnesium chloride with N-Cbz-4,5-diphenyl-1,2,3-oxathiazolidine-2-oxide 2 to afford the optical pure tert-butylsulfinyl-4,5-diphenyl-1,3-oxazolidinone 5 via an 1,5-alkoxy anion rearrangement, which is then subject to ammonia hydrolysis with LiNH2 in liquid ammonia to give (R)-tert-butanesulfinamide 6.